2019
DOI: 10.1101/852335
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hormonal control of motivational circuitry orchestrates the transition to sexuality in Drosophila

Abstract: 10Newborns and hatchlings of many species perform incredibly sophisticated behaviors, but all 11 vertebrates and many invertebrates selectively abstain from sexual activity at the beginning of life. 12Hormonal changes have long been associated with adolescence, but it is not clear how these 13circulating factors create a new motivation and drive its associated behaviors. We show that the 14 transition to sexuality in male Drosophila is controlled by juvenile hormone, which spikes at 15 eclosion and declines ov… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…JH titer is maximal around the time that adult flies eclose and then falls rapidly within the first 72 h of adulthood (Bownes and Rembold, 1987;Zhang et al, 2019), a time course similar to the observed decrease in a 0 /b 0 KC activity (Figure 1F). To gain insight into the developmental time window in which JH signaling exerts its effects on KC spontaneous activity, we restricted the knockdown of Met and Gce in KCs to an early post-eclosion period (day 0-2) or a period late in the first week of adulthood (day 4-7) with the temperature sensitive repressor tub-GAL80 ts (McGuire et al, 2003).…”
Section: Articlesupporting
confidence: 64%
See 2 more Smart Citations
“…JH titer is maximal around the time that adult flies eclose and then falls rapidly within the first 72 h of adulthood (Bownes and Rembold, 1987;Zhang et al, 2019), a time course similar to the observed decrease in a 0 /b 0 KC activity (Figure 1F). To gain insight into the developmental time window in which JH signaling exerts its effects on KC spontaneous activity, we restricted the knockdown of Met and Gce in KCs to an early post-eclosion period (day 0-2) or a period late in the first week of adulthood (day 4-7) with the temperature sensitive repressor tub-GAL80 ts (McGuire et al, 2003).…”
Section: Articlesupporting
confidence: 64%
“…Specifically, we find that a 0 /b 0 KCs exhibit sensorimotor-independent, TTX-insensitive asynchronous activity in young animals that is mediated by Cac voltagegated calcium channels. JH signaling in a young animal sensitive period, when the titer of JH circulating is high (Bownes and Rembold, 1987;Zhang et al, 2019), is required to achieve the mature, low KC activity state and enhance learned behavior. Our discovery that a hormone triggers a neural activity state transition essential for robust learning provides a model for mechanistically probing the maturation of learning circuits and behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In insects, hormones are typically assumed to regulate sexual behavior by activating existing neural circuits that control processes such as sexual maturation, memory formation and pheromone communication (11,(27)(28)(29). Recently, it has been shown that hormones can also regulate sexual motivation by repressing activation of existing neural circuits (5). It remained unclear, however, whether exposure to different levels of hormones earlier in development could organize neural circuits that affect sexual behavior in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal changes in temperature and photoperiod can serve as important cues that alter hormone levels and sexual behavior in a wide range of vertebrate and invertebrate taxa (4). Precisely how hormone signaling influences sexual behavior in most animals however, is not well known (5).…”
Section: Introductionmentioning
confidence: 99%